Pengaruh Transformasi Sistem E-Learning Terhadap Minat Belajar Siswa Sekolah Menengah Kejuruan (Smk) Wikrama Di Kota Bogor - Iskandar Abubakar; Gina .; Cahyono T Wibowo (Jurnal Komunikasi Pembangunan, 2014)
ABSTRACTE-Learning is a learning process electronically and remotely can be done without face to face  interactions  informally  with  a simpler,  for example  by means of  mailing lists,  e-newsletters  or  personal  websites,  organizations  and  companies that  want to  socialize services,  programs,  knowledge  or  particular  skills  in  societies.This study  was to determine the  e-learning  teaching system,  determine the effect of  the transformation of  e-learning system  to  students,  and  students'  interest in learning  to know  the  e-learning system. This  research  using  quantitative methods  with a  sample of  60  students.  Data collected through  questionnaires.  Analysis of  the data  using  product moment  The results showed  that the  learning  system  of e-learning  considered less  effective  as  face-to-face communication  is still  used  only  used  to  provide  enrichment  and  test  materials.  Effect of the transformation of  the system  of e-learning  relatively new,  so it is still  weak  and  the students  themselves have not  understood  in depth.  Student interest  to  study e-learning systems  is still  low because  of e-learning is still  in the  introduction  stage.  Effect of  the transformation of e-learning system  on  student interest  is very  weak  because it  is still using the system dependence learn face to face with the teacher.Key Words: E-Learning, Communication, Student